Bustling public communication by astronomers around the world driven by personal and contextual factors - Entradas, M.; Bauer, M. W. (Nature Astronomy, 2019)
Astronomers have a long tradition of outreach to satisfy public enthusiasm about stars and the Universe. Anecdotal evidence shows that astronomers love to popularize, and their efforts reach millions around the world. Yet no systematic comparisons of these activities may be performed without robust evidence. The general literature on scientists’ outreach finds barriers that discourage outreach, such as lack of fun, time, skills or recognition, or the perception that it lies outside of the professional role4 and is a risk to reputation—the ‘Carl Sagan effect’. It also finds that outreach is generally more frequent among the most senior and academically productive male scientists. Here, we present a study of n = 2,587 members of the International Astronomical Union with a 30% response rate. This is the largest systematic study of astronomers’ outreach activities beyond local case studies, which reveals how these factors compare within this community and in different research systems and environments. We show regional variations of outreach activity, with higher activity among astronomers in South America and Africa, and find that personal factors are important, yet contextual factors matter too. Among astronomers, gender, rewards and fear of peer criticism do not matter. Future research should focus on explanatory factors inherent to the ecology of scientific work, to better understand what drives scientists within their specific cultural and research environments.